The Growth And Laccase Activity of Edible Mushrooms in Plastics Degradation - Hing, Wai Lum (2018)
Plastics bring lots of benefit and harms to human and environment. Plastics have been widely used and produced in large scale since 1950s. There are different types of plastics materials such as low-density polyethylene (LDPE) and polystryrene which could be found in our daily life usage like plastic bag or food container (Siddiqui, Gondal & Redhwi, 2008).Plastics contains plasticizer such as Bisphenol A (BPA) or phthalate which is potential harmful to human health as both BPA and phthalate can be function as endocrine disrupting agents (North & Halden, 2013)